we know that
if two lines are perpendicular, then the product of their slopes is equal to minus one
so
![m1*m2=-1](https://tex.z-dn.net/?f=m1%2Am2%3D-1)
Step 1
<u>Find the slope of the given line</u>
we have
![3y=-4x+2](https://tex.z-dn.net/?f=3y%3D-4x%2B2)
Solve for y
Divide by
both sides
![3y/3=(-4x+2)/3](https://tex.z-dn.net/?f=3y%2F3%3D%28-4x%2B2%29%2F3)
![y=-\frac{4}{3}x+ \frac{2}{3}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B4%7D%7B3%7Dx%2B%20%5Cfrac%7B2%7D%7B3%7D)
the slope of the given line is ![m1=-\frac{4}{3}](https://tex.z-dn.net/?f=m1%3D-%5Cfrac%7B4%7D%7B3%7D)
Step 2
<u>Find the slope of a line that is perpendicular to the given line</u>
we have
![m1=-\frac{4}{3}](https://tex.z-dn.net/?f=m1%3D-%5Cfrac%7B4%7D%7B3%7D)
![m1*m2=-1](https://tex.z-dn.net/?f=m1%2Am2%3D-1)
![m2=-1/m1](https://tex.z-dn.net/?f=m2%3D-1%2Fm1)
substitute the value of m1
![m2=-1/(-4/3)=\frac{3}{4}](https://tex.z-dn.net/?f=m2%3D-1%2F%28-4%2F3%29%3D%5Cfrac%7B3%7D%7B4%7D)
therefore
<u>the answer is</u>
the slope is ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
Answer:
- 3*2=
![\sf{\pink{\dfrac{4}{5}}}](https://tex.z-dn.net/?f=%5Csf%7B%5Cpink%7B%5Cdfrac%7B4%7D%7B5%7D%7D%7D)
Step-by-step explanation:
<u>Given</u><u> </u><u>that</u><u>,</u><u> </u>
x*y=![\dfrac{(2x-y)}{(x+y}](https://tex.z-dn.net/?f=%5Cdfrac%7B%282x-y%29%7D%7B%28x%2By%7D)
<h3>
<u>SO</u><u>,</u><u> </u></h3>
3*2=
![\dfrac{2(3)-2}{3+2}\\\\\dfrac{6-2}{5}\\\\\dfrac{4}{5}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%283%29-2%7D%7B3%2B2%7D%5C%5C%5C%5C%5Cdfrac%7B6-2%7D%7B5%7D%5C%5C%5C%5C%5Cdfrac%7B4%7D%7B5%7D)
<u>Therefore</u><u>:</u><u>-</u>
![\therefore {3*2}=\dfrac{4}{5}](https://tex.z-dn.net/?f=%5Ctherefore%20%20%7B3%2A2%7D%3D%5Cdfrac%7B4%7D%7B5%7D)
Answer its 82 i added the cm
Important: 35x2 12x − 36 is not an equation; to obtain an equation, you must set <span>35x2 12x − 36 = to 0:
</span><span>35x^2 + 12x − 36 = 0. Also, "the square of x" must be represented by "x^2," and you must insert either the + or the - sign in front of the term 12x.
I am assuming that you meant </span>35x^2 + 12x − 36 = 0.
If that is indeed the case, then a = 35, b = 12 and c = -36
and the discriminant is b^2 - 4ac, or (12)^2 - 4(35)(-36) = 5184.
Since the discriminant is positive, this equation has 2 real, unequal solutions. They are
-12 plus or minus sqrt(5184)
x = -----------------------------------------
2(35)
Answer:
x+3 = x+3
Step-by-step explanation:
No matter what you plug into x, both sides will be the same.